Army biometric applications : identifying and addressing sociocultural concerns - Woodward, John D., Jr.; United States. Army.; Arroyo Center (Santa Monica, CA : Rand, 2001)
Every human possesses virtually infallible forms of identification. Known as biometrics, examples include fingerprints. The US Army has undertaken an assessment of how it can use biometrics to improve security, efficiency and convenience. This report examines the sociocultural concerns that arise.
Preface; Figures; Tables; Summary; Acknowledgments; Acronyms Chapter One: INTRODUCTION; Chapter One: INTRODUCTION; Chapter Two: A PRIMER ON BIOMETRIC TECHNOLOGY; Chapter Three: WHAT CONCERNS DO BIOMETRICS RAISE AND HOW DO THEY DIFFER FROM CONCERNS ABOUT OTHER IDENTIFICATION METHODS; Chapter Four: WHAT STEPS CAN THE ARMY TAKE TO ADDRESS THESE CONCERNS?; Chapter Five: WHAT IS THE FEASIBILITY OF A NATIONAL BIOMETRIC CENTER?; Chapter Six: CONCLUSIONS AND RECOMMENDATIONS; A. BIOMETRICS: A TECHNICAL PRIMER; B. PROGRAM REPORTS.
"Prepared for the United States Army."
"Arroyo Center."
"MR-1237."
Includes bibliographical references (pages 173-185).
Print version record.
eBooks on EBSCOhost
Keywords: United States. -- Army -- Personnel management; United States. -- Army; Biometric identification -- United States; Identification biométrique -- États-Unis.; TECHNOLOGY & ENGINEERING -- Military Science; HISTORY -- Military -- Other; BUSINESS & ECONOMICS -- Human Resources & Personnel Management; Biometric identification; Armed Forces -- Personnel management; United States